Off the map : a novel - Doller, Trish (Doller, Trish. Beck sisters, 2023)
"On the road to love, you don't need a GPS... Carla Black's life motto is "here for a good time, not for a long time." She's been traveling the world on her own in her vintage Jeep Wrangler for nearly a decade, stopping only long enough to replenish her adventure fund. She doesn't do love and she doesn't ever go home. Eamon Sullivan is a modern-day cartographer who creates digital maps. His work helps people find their way, but he's the one who's lost his sense of direction. He's unhappy at work, recently dumped, and his one big dream is stalled out--literally. Fate throws them together when Carla arrives in Dublin for her best friend's wedding and Eamon is tasked with picking her up from the airport. But what should be a simple drive across Ireland quickly becomes complicated with chemistry-filled detours, unexpected feelings, and a chance at love--if only they choose it"--